African Yam Bean - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2023)
The African yam bean, a highly nutritious and versatile legume native to West Africa, has been a vital source of sustenance and income for local communities for centuries. This documentary delves into the fascinating history and cultural significance of the African yam bean, while also highlighting its potential as a solution to global food insecurity and malnutrition.